EVALUASI SIMPUS MedCis KIA (SITEM INFORMASI MANAJEMEN PUSKESMAS MedCis KESEHATAN IBU DAN ANAK) (LB3) DI TERKAIT PEMBUATAN LAPORAN PUSKESMAS DANUREJAN II - , IKA MUTMAINATUN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Lately management information systems (SIM) is starting to be developed and implemented as hospital management information system and hospital information systems in health centers using the health centers (SIMPUS) in which the existence of the application MedCis SIMPUS very helpful in facilitating the work of the health center in the medical recorder Health Center. However work finishing at the health center in the second part of KIA Danurejan didnât use SIMPUS MedCis in entering patient examination results and is not used in making the report LB3 Objective: To determine the implementation SIMPUS mother and child health (KIA) in Health Center II Danurejan, to know the factors inhibiting the implementation of SIMPUS MedCis KIA in Danurejan Health Center from terms of human resources, software, hardware and to know reporting process KIA (LB3)-based manual Danurejan walk in health center II. Research methodology: The kind of this research used descriptive qualitative study with a phenomenological approach. The subject of this research is the Medical Record officer and clerk at the health center KIA II Danurejan. The objectf is SIMPUS MedCis implementation activities and reports preparing. Results: implementation of patient data entry KIA is only done when the patient register, social data entry is done by KIA patient medical record officer entries piece of data in the registration. Inhibiting fators of the implementation SIMPUS MedCis KIA is human resources because there has never been an official training and the item in software because it is not matched with a report that is requested by the department. Preparation of a report on the health center II Danurejan use manual forms and electronic equipment such as computers in the form of a report PWS Microsoft Excel format.